FRAMING ANALYSIS OF THE ZERO WASTE CAMPAIGN ON THE TIKTOK ACCOUNT @PANDAWARAGROUP - Anggraeni, Saskya Dewi; Istiqomah (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The zero waste campaign phenomenon on TikTok has become a focus of global efforts to reduce the environmental impact of waste. Pandawaragroup is a community actively campaigning for this movement on TikTok. Pandawaragroup's distinctive content revolves around environmental cleanliness, particularly waters polluted by waste. Previous research has demonstrated how media can be used to convey environmental messages and raise public awareness of sustainability issues. This study aims to examine the framing applied by the TikTok account @pandawaragroup in conveying the zero waste campaign message. The theory used in this study is the framing theory of Gamson and Modigliani. Method: The methodology used is qualitative with a descriptive approach, where researchers analyzed videos uploaded to the TikTok account @pandawaragroup. Data were collected through direct observation of the videos and mapping emerging themes related to the zero waste campaign. Result: The results of this study indicate that the framing of the zero waste campaign on social media can influence audience understanding and behavior in dealing with environmental issues, especially among Generation Z TikTok users. Novelty: This study contributes novelty by identifying specific framing devices in short video social media content, an area less explored compared to traditional and artistic media campaigns, while highlighting TikTok’s potential as an interactive medium for environmental communication.